Systematic Review: Syndromes, Early Diagnosis, and Treatment in Autoimmune Encephalitis - Hermetter, Christina; Fazekas, Franz; Hochmeister, Sonja (Frontiers in Neurology, 2018)
In recent years, new antibodies have been discovered which mediate autoimmune encephalitis. This immunological response can be triggered by an infection or a tumor. Classical onconeuronal antibodies are directed against intracellular neuronal agents but recently, a novel group of antibodies to neuronal cell-surface and synaptic antigens associated with different CNS-syndromes, has been discovered. Interestingly, the syndromes in this group can be successfully treated with immunotherapy and frequently do not have underlying tumors. The aim of this review is to describe the current state of knowledge about autoimmune encephalitis, in order to provide clinicians with a concise, up-to-date overview. Thus, a comprehensive literature search was performed in medical databases. The literature was carefully studied and new findings focusing on the symptoms, diagnosis and treatment were summarized and interpreted. Even though it might be challenging in some cases, the awareness of certain symptom constellations and demographic information, in combination with laboratory- and MRI-results, allows clinicians to make the diagnosis of probable autoimmune encephalitis at an early stage. Treatment can therefore be initiated faster, which significantly improves the outcome. Further investigations could define the underlying pathogenic mechanisms. Randomized controlled trials, paired with increasing clinical experience, will be necessary to improve the identification of affected patients, treatment strategies, and outcomes in the years to come.